Disease-related distress, self-care and clinical outcomes among low-income patients with diabetes. Issue 6 (31st January 2014) - Pandit, Anjali U; Bailey, Stacy C; Curtis, Laura M; Seligman, Hilary K; Davis, Terry C; Parker, Ruth M; Schillinger, Dean; DeWalt, Darren; Fleming, David; Mohr, David C; Wolf, Michael S
Abstract : Background: The purpose of this study is to determine the prevalence of diabetes distress and its relationship with health behaviours and clinical outcomes in low-income patients. Methods: Secondary analyses were conducted using baseline data from a clinical trial evaluating a diabetes self-management intervention. Interviews were conducted with 666 participants receiving care at nine safety net clinics in Missouri. Distress was measured using the Diabetes Distress Scale, and outcomes included medication adherence, physical activity, nutrition and clinical biomarkers (haemoglobin A1C (HbA1C), blood pressure, low-density lipoprotein (LDL) cholesterol). Results: In a sample of 666 participants, 14.1% and 27.3% of patients were identified as highly and moderately distressed, respectively, with higher rates among younger, female and lower income patients. When compared with moderately and no distress groups, highly distressed patients were less adherent to medications (20.7% vs 29.9% vs 39.4%, p<0.001) and had higher HbA1C values (9.3% (SD=2.0) vs 8.2% (SD=1.8) vs 7.8% (SD=1.7), p<0.001), diastolic blood pressure (81.8 (SD=9.4) vs 80.2 (9.7) vs 78.9 (SD=8.8), p=0.02) and LDL cholesterol (104.6 (SD=42.4) vs 97.2 (34.3) vs 95.5 (37.9)) In multivariable analyses, high and moderate distress were associated with lower medication adherence (OR=0.44; 0.27 to 0.23, p=0.001) and (OR=0.58; 0.42 to 0.79; p=0.001), respectively, and higher HbA1C in only the highly distressed group (B=1.3; 0.81 to 1.85; p<0.001) compared with the no distress group. Conclusions: Diabetes distress is prevalent and linked to poorer adherence to health behaviours and glycemic control in a sample of patients receiving care from low-income clinics.